Dental age assessment in Caucasian subjects with third molar agenesis - Abu Alhaija Elham S.; Derbash Aftima A.; Al-Khateeb Susan N. (Sciendo, 2017)
Delayed dental development has been linked with tooth agenesis. Research aimed at dental age estimation in subjects with third molar agenesis has been minimal.